1990
DOI: 10.1002/ajmg.1320350111
|View full text |Cite
|
Sign up to set email alerts
|

Partial deletion of the long arm of chromosome 11 [del(11)(q23.3→qter)] with abnormal white matter

Abstract: A patient with partial deletion of the long arm of chromosome 11[del(11)(q23.3----qter)] had macrocephalic trigonocephaly, growth and mental retardation, congenital heart defect, and characteristic facial appearance familiar to that of 33 other reported patients with this deletion. Computed tomography (CT) and magnetic resonance imaging of this infant's brain demonstrated abnormality of the supratentorial white matter. This may represent either deficiency or delay in myelination or possibly a demyelination pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…Therefore, haploinsufficiency of MBP has been suggested to be responsible for white matter abnormalities seen in 18qϪ patients. The specificity of these findings has been questioned (11), because white matter changes are frequently found in other malformation syndromes as well, like in chromosome 11q and 14q deletions (12)(13)(14)(15)(16). However, the hypothesis of MBP haploinsufficiency was supported by Gay et al (17) who, using fluorescence in situ hybridization (FISH), found incomplete myelination in all 18qϪ patients with one copy of the MBP gene, while a single patient with two copies of the MBP gene had normal MRI.…”
mentioning
confidence: 99%
“…Therefore, haploinsufficiency of MBP has been suggested to be responsible for white matter abnormalities seen in 18qϪ patients. The specificity of these findings has been questioned (11), because white matter changes are frequently found in other malformation syndromes as well, like in chromosome 11q and 14q deletions (12)(13)(14)(15)(16). However, the hypothesis of MBP haploinsufficiency was supported by Gay et al (17) who, using fluorescence in situ hybridization (FISH), found incomplete myelination in all 18qϪ patients with one copy of the MBP gene, while a single patient with two copies of the MBP gene had normal MRI.…”
mentioning
confidence: 99%
“…Taysi et al observed trisomy of the long arm of Chromosome 1 in patients manifesting mental retardation and growth malformations (Taysi & Sekhon, ). The deletion of q23 to qter region of Chromosome 11 has also been associated with mental retardation, cognitive, and developmental defects (Wardinsky, Weinberger, Pagon, Clarren, & Thuline, ). Similar neurocognitive and behavioural defects were manifested in individuals containing deletion of the 11q23 to qter region (Akshoomoff, Mattson, & Grossfeld, ; Coldren et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(Taysi & Sekhon, 1978). The deletion of q23 to qter region of Chromosome 11 has also been associated with mental retardation, cognitive, and developmental defects (Wardinsky, Weinberger, Pagon, Clarren, & Thuline, 1990). Similar neurocognitive and behavioural defects were manifested in individuals containing deletion of the 11q23 to qter region (Akshoomoff, Mattson, & Grossfeld, 2015;Coldren et al, 2009 Therefore, the exact mechanisms involved in this unexpected outcome need to be investigated thoroughly.…”
Section: Discussionmentioning
confidence: 99%
“…β1, β3 and N-CAM all possess immunoglobulin domains which may interact with extracellular matrix molecules. Deletions of chromosome 11 from 11q23 to the terminus have been shown to be associated with delayed myelination or demyelinating diseases [20,33] which could be associated with loss of β2, β3 or N-CAM genes. A mutation in the related β1 gene, SCN1B, is associated with febrile seizures and generalized epilepsy [31].…”
Section: Discussionmentioning
confidence: 99%